Avaliação de sintomas e fatores associados ao Transtorno de Estresse Pós-Traumático em profissionais do serviço de atendimento móvel de urgência em Três Lagoas-MS - Jamila de Lima Gomes (2022)
Introduction: Post Traumatic Stress Disorder (PTSD) is a syndrome in which a person, after experiencing or witnessing a traumatic event, develops thoughts or nightmares that systematically relive the trauma. That could be associated with physical symptoms, such as insomnia, irritation, numbness, or emotional disorder, lasting between a month to several years after the event. Professionals who work at the pre-hospital service, more specifically, at the Mobile Emergency Care Service (MECS), are exposed to frequent accidents of the most diverse types, causing great emotional distress, which in many of them, leads to the development of problems such as anxiety, phobias, and drug abuse, or even more severe disorders such as PTSD. Objective: To contextualize the current scenario related to the prevalence of symptoms and factors associated with PTSD in professionals working at MECS in Três Lagoas – MS. Methods: A field study, exploratory and descriptive, was carried out, with a quantitative-qualitative approach. Data collection was conducted through a semi-structured questionnaire that addressed socioeconomic, demographic, employment, traumatic, and behavioral variables, and the PTSD Checklist (PCL-5), a validated psychometric scale to assess the presence and severity of PTSD symptoms. The instruments were applied to professionals from MECS of Três Lagoas – MS (n=56), from November 2020 to January 2021. The answers to the discursive questions were categorized in terms of content and analyzed using a descriptive form. Categorical variables were analyzed using an association test, by Chi-square or Fisher's Exact Test, subsequently submitted to the application of univariate binomial logistic regression models, with the calculation of the unadjusted odds ratio as an additional measure of the probability of occurrence. Continuous data were evaluated by the Mann-Whitney test. A significance level of p < 0,05 was adopted for the statistical analyzes. The project was approved by the Research Ethics Committee/UFMS (CAAE 28449620.7.0000.0021, technical statement 4.216.396). Results: the population evaluated shows a high prevalence of symptoms associated with PTSD (62,5%). The presence of symptoms and increased risk for the development of the disorder were associated with: higher monthly income; occurrence of previous traumatic events; active search for help after trauma; the need for time off work; use of psychotropic drugs; change in the pattern of drugs abuse; the presence of a family history of psychiatric disorders, and; current living with PTSD-related symptoms. Conclusion: the data reinforce the occupational risk associated with professionals working in emergency service, with more impact on mental health and determination of factors most associated with susceptibility to the disorder. The research reinforces the need for changes aimed at increasing the visibility of occupational risk among these professionals and improving the support offered to them, seeking better performance in the work environment and life quality. The relevance of PTSD in work activities in the health context signals the importance of promoting programs and training on the disease, forms of prevention and interventions in the work environment, and critical points of action of the nursing team.